Using Feedback Control to Control Rotor Flux and Torque of the DFIG-Based Wind Power System - Ali Nadhim Jbarah Almakki (International Journal of Engineering and Technology Innovation, 2023)
Direct torque control (DТС) is a method of controlling electrical machines that are widely used, and this is due to its simplicity and ease of use. However, this method has several issues, such as torque, rotor flux, and current fluctuations. To overcome these shortcomings and improve the characteristics and robustness of the DTC strategy of the doubly-fed induction generator (DFIG), a new DTC scheme based on the feedback control method (FCM) and space vector modulation (SVM) is proposed. In the proposed DTC technique, a proportional-integral controller based on feedback control theory is used to control and regulate the torque and rotor flux of the DFIG. On the other hand, the SVM technique is used to control the rotor side converter (RSC) to obtain a high-quality current. The simulation result shows that the proposed DTC technique has the advantages of faster dynamics and reduced harmonic distortion of current compared to the ‎conventional technique.‎